Expression of Tumor Necrosis Factor Receptor 2 Characterizes TLR9-Driven Formation of Interleukin-10-Producing B Cells - Ticha, Olga; Moos, Lukas; Wajant, Harald; Bekeredjian-Ding, Isabelle (Frontiers in Immunology, 2018)
B cell-derived IL-10 production has been described as a hallmark for regulatory function in B lymphocytes. However, there is an ongoing debate on the origin of IL-10 secreting B cells and lack of specific surface markers has turned into an important obstacle for studying human B regulatory cells. In this study we propose that TNFR2 expression can be used for purification of IL-10-secreting B cells. Our data confirm that IL-10 production can be induced by TLR9 stimulation with CpG ODN and that IL-10 secretion accompanies differentiation of peripheral blood B cells into plasma blasts. We further show that CpG ODN stimulation induces TNFR2 expression, which correlates with IL-10 secretion and terminal differentiation. Indeed, flow cytometric sorting of TNFR2+ B cells revealed that TNFR2+ and TNFR2- fractions correspond to IL-10+ and IL-10- fractions, respectively. Furthermore, CpG-induced TNFR2+ B cells were predominantly found in the IgM+ CD27+ B cell subset and spontaneously released immunoglobulin. Lastly, our data corroborate the functional impact of TNFR2 by demonstrating that stimulation with a TNFR2 agonist significantly augments IL-10 and IL-6 production in B cells. Altogether, our data highlight a new role for TNFR2 in IL-10 secreting human B lymphocytes along with the potential to exploit this finding for sorting and isolation of this currently ill-defined B cell subset.